Analysis of Intrinsic Motivation Meaning in Song Lyrics "Mulai Langkahmu" by Yura Yunita - Santi Kurnia; Muhamad Ekhsan (Journal of Research in Business, Economics, and Education, 2021)
This study aims to explain the meaning of intrinsic motivation contained in the lyrics of the song "Mulai Langkahmu" by Yura Yunita. This research is a type of qualitative research with semiotic analysis of Ferdinand de Saussure to find markers and signifiers of the meaning of intrinsic motivation to be conveyed by the poet. The result of this research is that the song ""Mulai Langkahmu" by Yura Yunita is a song that contains the meaning of intrinsic motivation which is intended for young people to struggle in reaching their dreams and goals. Young people are a golden generation that is rich with creative thoughts and ideas, so never give up and surrender in realizing all these thoughts and ideas. Good changes will happen if young people are willing to move and fight.